2020
DOI: 10.1002/ijgo.13351
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum CRH/5‐HT ratio for postpartum depression

Abstract: Objective: To analyze the changes in the serum levels of CRH and 5-HT in women with postpartum depression (PPD) and to study the value of the CRH/5-HT ratio for the prediction of PPD. Methods: This prospective study recruited pregnant women from the Fourth Affiliated Hospital, China Medical University between January 2017 and October 2019. Women were considered for inclusion if they had no history, or no current evidence, of a psychiatric disorder. All women were assessed at postpartum day 10 with the Edinburg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…In a study involving TPH2 knock-out mice, lack of 5-HT affected the normal connections of neurons in the brain, leading to neurodevelopmental disorders [ 27 ]. Other studies have shown that postpartum depression patients have significantly lower levels of 5-HT, and this can lead to mood and behavior control disorders [ 28 , 29 ]. Abnormal metabolism of 5-HT is one of the classic mechanisms of depression, and the antidepressant fluoxetine plays its role by raising 5-HT levels in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving TPH2 knock-out mice, lack of 5-HT affected the normal connections of neurons in the brain, leading to neurodevelopmental disorders [ 27 ]. Other studies have shown that postpartum depression patients have significantly lower levels of 5-HT, and this can lead to mood and behavior control disorders [ 28 , 29 ]. Abnormal metabolism of 5-HT is one of the classic mechanisms of depression, and the antidepressant fluoxetine plays its role by raising 5-HT levels in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cao S et al (2020) found that the serum levels of CRH was significantly higher in women with postpartum depression (PPD) than in the non-PPD group. The authors offered that the serum levels of CRH and serotonin may serve as a potential early marker for identifying women at high risk for PPD 11 . To date, there are practically no studies devoted to determine the serum levels of CRH in vitiligo patients.…”
mentioning
confidence: 99%
“…Shimizu et al found no significant correlation between cortisol level and scale test scores ( 60 ), and Labad et al found no correlation between cortisol, CRH, or ACTH concentration and EPDS scores ( 42 ). Of the five studies in which the cutoff value was 13 or higher, two demonstrated a significant correlation between blood CRH and postpartum depressive symptoms or EPDS score ( 37 , 38 ), and one demonstrated a positive correlation between morning cortisol level and severity of depression ( 43 ). The remaining two studies revealed no relationship between CRH concentration and PPD; they were conducted with ELISA test kits for serum and CSF samples rather than radioimmunoassay, which is highly sensitive ( 36 , 41 ).…”
Section: Assessments For Depression Screeningmentioning
confidence: 99%
“…In all studies of the role of HPA axis stress hormones in PPD, the aforementioned questionnaires were used for diagnosis in the participants, not only because each assessment generally took less than 15 min to finish but also because the sensitivity and specificity of the tests had been validated ( 30 , 70 , 72 , 74 ). To overcome cultural differences and difficulties in understanding of these tests, the EPDS, BDI, and many other questionnaires have been translated into several languages and applied in different countries ( 37 , 42 , 60 ). However, even within a country or similar cultural background, different research groups may adopt different thresholds according to the aims of their studies.…”
Section: Assessments For Depression Screeningmentioning
confidence: 99%
See 1 more Smart Citation